Lung Transplantation for Late-Onset Pulmonary Hypertension in a Patient with Congenital Diaphragmatic Hernia - Chiara Iacusso; Francesco Morini; Irma Capolupo; Andrea Dotta; Stefania Sgrò; Francesco Parisi; Adriano Carotti; Pietro Bagolan (Georg Thieme Verlag KG, 2018)
Lung hypoplasia and pulmonary hypertension (PH) in association with congenital diaphragmatic hernia (CDH) may cause fatal respiratory failure. Lung transplantation (Ltx) may represent an option for CDH-related end-stage pulmonary failure. The aim of this study is to report a patient with CDH who underwent Ltx or combined heart-lung transplantation (H-Ltx). Our patient was born at 33 weeks of gestation, with a prenatally diagnosed isolated left CDH. Twenty-four hours after birth, she underwent surgical repair of a type D defect (according to the CDH Study Group staging system). Postoperative course was unexpectedly uneventful, and she was discharged home at 58 days of life. Echocardiography before discharge was unremarkable. Periodic follow-up revealed gastroesophageal reflux (GER) and initial scoliosis. At the age of 10, she was readmitted for severe PH. Lung function progressively deteriorated, and at the age of 14, she underwent H-Ltx due to end-stage respiratory failure. After discharge, she developed recurrent respiratory tract infections, severe malnutrition, and drug-induced diabetes. Scoliosis and GER progressed, requiring posterior vertebral arthrodesis and antireflux surgery, respectively. Bronchiolitis obliterans further impaired her respiratory function, and though she had a second Ltx, she died at the age of 18, 4 and 1.5 years after the first and the second Ltx, respectively. Late-onset PH is an ominous complication of CDH. From our patient and the six further cases collected from the literature, Ltx may be considered as a last-resource treatment in CDH patients with irreversible and fatal respiratory failure, although its prognosis seems unfair.